Bioactive sorbicillinoid derivatives from an endophytic fungus Trichoderma citrinoviride - Xia, Yan-Ping; Xie, Yan; Rao, Li; Yin, Guo-Ping (Frontiers in Microbiology, 2025)
Three new sorbicillinoid derivatives, citrinsorbicillinol A-C (1–3), along with three known compounds, such as trichosorbicillin G (4), dibutyl phthalate (5), and 3-(4-methoxyphenyl) propanoic acid (6), were isolated from the endophyte Trichoderma citrinoviride of Coptis chinensis. Their structures were elucidated through extensive analyses of spectroscopic data, computer-assisted structure elucidation (ACD/Structure Elucidator), density functional theory (DFT) calculations of the nuclear magnetic resonance (NMR) spectra, and electronic circular dichroism (ECD). Biologically, compounds 1–4 exhibited potential antioxidant activity, as assessed using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) assay, with IC50 values ranging from 27.8 to 89.6 μM. In particular, compounds 2 and 3 demonstrated radical scavenging activity comparable to that of the positive control, ascorbic acid, with IC50 values of 27.8 and 31.2 μM, respectively. Moreover, compound 1 exhibited potential anti-inflammatory activity by inhibiting nitric oxide (NO) production in lipopolysaccharide (LPS)-induced RAW 264.7 macrophages, with an IC50 value of 52.7 μM. These findings underscore the therapeutic potential of the new sorbicillinoid derivatives for antioxidant and anti-inflammatory applications.